Assessing the Current Competencies of Science Subject Teachers in Practical/Laboratory Work in Secondary Schools of Hyderabad District (Al-Qamar, 2025)
The study looked into descriptive research to evaluate the existing conditions of the science laboratories in the government secondary schools of Hyderabad District. This study is concerned to identify the problems faced by the science teachers and students in teaching and learning of science due to non-functionality of science laboratories in government secondary schools. The study focused on the objectives; to find out the availability of facilities in the laboratories of government secondary schools for science teachers and students, to assess the current competencies of science subjects’ teachers in practical/laboratory work in government secondary schools and to find out the problems faced by science subject teachers in carrying out practical work in laboratories. The population for the research project comprised of science teachers, science students, headmasters and science lab staff of government secondary schools of Hyderabad District. The sample was randomly selected from four talukas (sub-divisions) Data was collected through questionnaire, interviews and observations. Both quantitative and qualitative data analysis approaches were used for data analysis. Main findings of the study were; there existed no good science laboratories in the government secondary schools, laboratories were not fully functional and science practicals seldom conducted, proper funds were not provided for the purchase of apparatus, teachers were not trained to conduct practicals, shortage of technical staff was also observed. science teachers should be trained to conduct science practicals, proper funds should be provided to the schools for purchase of science apparatus, shortage of technical staff should be overcome.
Keywords: Secondary Science Laboratory, Science Student